Immune crosstalk in Alzheimer’s and Parkinson’s disease: insights from Drosophila models into the brain–peripheral immune axis - Parvez, Faiza; Rahul, (Frontiers in Immunology, 2026)
BackgroundNeurodegenerative diseases (NDs) such Alzheimer’s disease (AD) and Parkinson’s disease (PD) are increasingly understood as systemic disorders driven by chronic neuroimmune dysregulation. The bidirectional communication between the central nervous system (CNS) and peripheral immune compartments is termed neuroimmune crosstalk, plays a pivotal role in disease initiation, progression, and therapeutic resistance. However, mammalian models often obscure mechanistic resolution due to immune redundancy and adaptive complexity.ObjectiveThis review highlights Drosophila melanogaster as a genetically tractable and evolutionarily conserved model for dissecting innate immune signaling and inter-organ communication in neurodegeneration. We emphasize its utility in resolving causality, identifying conserved cytokine pathways, and modeling systemic inflammation relevant to Parkinson’s and Alzheimer’s disease.Key findingsDrosophila possesses a tripartite immune system that is brain-resident glia, circulating hemocytes, and the fat body that coordinates responses via Toll, Immune deficiency (Imd), JAK/STAT, and MAPK pathways. Glial cells engage in Draper-mediated phagocytosis and NF-κB/Relish signaling, while peripheral immune components modulate CNS integrity through cytokines such as Unpaired 3 (Upd3) and Eiger. Furthermore, hyperactivation of the Imd pathway’s NF-κB homolog, Relish, within the CNS drives neurodegeneration via the neurotoxic effects of Antimicrobial Peptides (AMPs). These mechanisms mirror mammalian neuroimmune dynamics and reveal conserved therapeutic targets.ConclusionDrosophila melanogaster offers unparalleled mechanistic clarity in modeling neuroimmune interactions. Its simplified immune architecture, precision genetics, and compatibility with multi-omics and AI-assisted phenotyping position it as a strategic complement to vertebrate models. Insights from Drosophila are redefining neurodegeneration as a multi-organ process and accelerating the development of inflammation-targeted therapies for ND.